Eksplorasi Etnomatematika Pada Rumah Adat Balla Lompoa Doman Kale Balla - Ahmad, Asdar; Ashari, Nur Wahidin (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2025)
This study explores the application of ethnomathematics in the traditional Balla Lompoa house, a cultural heritage of the Gowa Kingdom. Ethnomathematics, as a branch of knowledge connecting mathematics with local culture, is used to analyze the architectural elements of the house. The focus of the research is on the Kale Balla section, with the aim of identifying the mathematical concepts embedded in the building's design, such as spatial proportions, geometric patterns, and symmetry in the house’s structure. The research employs an ethnographic methodology with a qualitative approach, involving observation, interviews, and literature review. The findings reveal that the Balla Lompoa house embodies values of balance, stability, and harmony through geometric shapes such as cubes, rectangles, and rhombuses. Furthermore, this study shows that ethnomathematics plays a role not only in education but also in preserving cultural knowledge and providing deeper understanding of the relationship between mathematics and culture in the Makassar community. This research highlights the importance of integrating ethnomathematical concepts in teaching to enhance contextual and culture-based mathematical understanding.